2022
DOI: 10.3390/nu14091956
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Meat and Vegetable Intake, Cooking Methods, and Asthenozoospermia: A Hospital-Based Case–Control Study in China

Abstract: Background: The role of meat and vegetable intake in the development of asthenozoospermia has been controversial, and the role of cooking methods for meat and vegetables in the association has yet to be determined. The present study aimed to illuminate the relationship between the consumption and cooking methods of meat and vegetables and the risk of asthenozoospermia. Methods: In this hospital-based case–control study, we enrolled 552 patients with asthenozoospermia and 585 healthy controls. Dietary informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 61 publications
1
10
0
Order By: Relevance
“…Second, dietary intake was collected through a semi-quantitative FFQ, which might lead to incorrect estimates of various nutrient intakes. However, the FFQ used in our study was verified by previous studies, with high validity and reliability ( Liu et al , 2022; Cui et al ., 2023 ). Third, the cases and controls of the present study were not a random sample of the entire target population, which could lead to admission rate bias.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Second, dietary intake was collected through a semi-quantitative FFQ, which might lead to incorrect estimates of various nutrient intakes. However, the FFQ used in our study was verified by previous studies, with high validity and reliability ( Liu et al , 2022; Cui et al ., 2023 ). Third, the cases and controls of the present study were not a random sample of the entire target population, which could lead to admission rate bias.…”
Section: Discussionsupporting
confidence: 87%
“…The validity and reliability of the FFQ have been verified in our previous studies ( Liu et al , 2021 ; Wang et al , 2021 ). For most food items, the Spearman correlation coefficients and intraclass correlation coefficients for reproducibility were above 0.5, and the correlation coefficients were 0.3–0.7 between the FFQ and weighed diet records ( Liu et al , 2022 ; Cui et al, 2023 ). All participants were asked to report their usual intake frequency of each food item with seven response options: almost never, two to three times per month, one time per week, two to three times per week, four to six times per week, one to two times per day, and more than two times per day.…”
Section: Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…At the same time, there is a large difference between the Z value of this intersection point and the above Z value range (50 ~ 58.55°C), showing the difference in sensitivity between human sensory and physical and chemical measurement methods. From the reported results (Li, 2015 ), it is found that the measurement results of the instrument and the sensory measurement of the human being are also quite different, and further research is needed.…”
Section: Resultsmentioning
confidence: 99%
“…Glycation end products can also be delivered to the body from outside, especially in food. Thermal treatment causes the formation of new AGEs, particullary in grilling, baking and frying, which may especially cause reduced sperm motility [17]. The study by Nevin et al analyzed the effect of AGE on sperm damage.…”
Section: Resultsmentioning
confidence: 99%